Relato de la Revolución y reflexión sobre la juventud urbana post Tlatelolco en Reed, México insurgente (Paul Leduc, 1970) - Pascual-Gutiérrez, Iris (Antropología. Revista Interdisciplinaria del INAH, 2023)
El final del movimiento estudiantil de 1968 generó en sus participantes desencanto, frustración y dudas respecto del camino político a seguir en el futuro. Una de las plasmaciones más características de este ambiente fue el cine filmado en medios universitarios e independientes entre Tlatelolco y 1970, del cual Reed, México insurgente (Paul Leduc, 1970) es un buen ejemplo. Ese largometraje presenta una visión estética y discursivamente renovada de la Revolución mexicana, al tiempo que invita a reflexionar sobre la situación y expectativas de la juventud urbana de clase media durante estos años.
Revolution’s narration and reflexión on urban post Tlatelolco’s youth in Reed, México insurgente (Paul Leduc, 1970)
The end of the 1968 student movement generated disenchantment, frustration and doubts among its participants regarding the political path to follow in the future. One of the most characteristic representations of this environment was the cinema filmed in universities and independent media between Tlatelolco and 1970, of which Reed, México insurgente (Paul Leduc, 1970) is a good example. This feature film presents an aesthetic and discursively renewed vision of the Mexican Revolution and invites you to reflect on the situation and expectations of the middle-class urban youth during these years.
Keywords: movimiento estudiantil de 1968; Revolución Mexicana; relaciones cine-historia; John Reed; cine independiente; 1968 student movement; Mexican Revolution; cinema-history relationship; independent cinema